Avaliação da relação entre fatores psicossociais e distúrbios osteomusculares:um estudo em uma empresa de calçados: um estudo em uma empresa de calçados - Silva, Jonhatan Magno Norte da (2016)
Currently, the most accepted model in the scientific community to explain the multifactorial origin of the pain is the biopsychosocial model. This model suggests that psychosocial factors also contribute to the onset of pain as well as physical / ergonomic factors. An branch important industrial of the secondary sector, the shoe industry has stood out negatively by the high number of work-related musculoskeletal disorders. Thus, the objective expected is investigate to the relationship between psychosocial factors and the development of musculoskeletal disorders related to work in production sectors of a great shoes industry. To achieve this objective, there was a systematic review in about 150 papers published in international journals with impact factor. We used the Nordic questionnaire to identify the symptoms of pain in the body segments. Psychosocial factors were evaluated by the scores of Job content questionnaire (JCQ) and the Effort-reward imbalance questionnaire (ERI), as well as other modern psychosocial factors, such as bullying, discrimination, job dissatisfaction, sexual harassment and stress. Quadrants were built to evaluate effect of the combination of demands (physical and psychological) with job control; and to evaluate the combination of effort and reward for the onset of pain. Ordinal logistic regression models were built relating the pain reported by employees and psychosocial factors, in order to verify the probability of a given psychosocial factors contribute to the emergence and worsening of pain in the worker's body. All body parts were affected by at least one psychosocial factor. It was observed that some psychosocial factors such as job dissatisfaction affect both sexes, leading to occurrence more frequent of pain in the wrist in men (OR = 2.61; 1.32-5.15) and women (OR = 3.88; 1.33-11.32). Factors such as stress, affect more men, leading to the appearance of more frequent pain (OR = 2.63; 1.26-5.45) and more intense pain (OR = 2.70; 1.32-5.52) in hands. Among women, other factors such as discrimination have impact on the appearance of more frequent pain (OR = 5.10; 1.52-17.13) and more intense pain (OR = 3.43; 1.15-10.23) in the neck. The quadrant that combines the high effort and low reward was the one that presented, for men, more risk for the appearance of frequent pain (OR = 14.35; 3.95-52.18) and intense pain (OR = 17.05; 4.61-63.12) in the neck; and more frequent pain (OR = 9.69; 2.30-40.79) and more intense (OR = 10.81; 2.58-45.23) at the head of women. Thus concluded that psychosocial factors may lead to the onset of pain in the regions of the human body.